Determinan Total Aset Bank Pembiayaan Rakyat Syariah (BPRS) di Jawa Timur Tahun 2009-2014 - Anton Sudrajat (Justicia Islamica, 2014)
To create a strong and robust Islamic rural bank (BPR Syariah) in East Java, it is necessary to support it with significant asset growth so that it can increase public trust in BPR Syariah. The purpose of this study is to determine the effect of financing, third-party funds (DPK), financing to deposit ratio, and non-performing financing on the total assets of BPR Syariah in East Java. The results of the study indicate that simultaneously and partially, the factors of Financing, Third Party Funds (DPK), Financing to Deposit Ratio (FDR), and Non-Performing Financing (NPF) have an influence on the total assets of Islamic Rural Banks in East Java.